The Relationship of Polimorpisms of Apolipoprotein E and Angiotensin Converting Enzyme Genotypes With Plasma Malondialdehyde Levels in Dementia Patients - Ağaçhan, Bedia; Yılmaz, Hülya; Kızıltan, Güneş; İsbir, Turgay (Fırat University, 2003)
Aim: In This Study, We Aimed Investigation Of Relationship Between Apolipoprotein E (Apo E) And Angiotensin Converting Enzyme (ACE) Genotypes And Plasma Malondialdehyde Levels In Dementia. Materials and method : We investigated the Apo E and ACE polymorphism in 47 patients with dementia and 29 healthy subjects. Polymerase Chain Reaction (PCR) and Restriction Fragment Length Polymorphism (RFLP), and agarose gel electrophoresis tecniques were used to determine these polymorphism. Plasma malondialdehyde (MDA) levels were determined spectrophotometrically. Results: We found that APO E4 (7.49±3.26 nmol/ml vs 5.6±2.5 nmol/ml ; p

Amaç: Bu çalışmanın amacı, Apolipoprotein E (APO E) ve Anjiotensin Konverting Enzim (ACE) genotiplerinin demansta plazma malodialdehid (MDA) düzeyleriyle ilişkili olup olmadığını araştırmaktı. Gereç ve yöntem: Bu çalışmada 47 demans tanısı konmuş hastada ve 29 sağlıklı kontrolde Apo E ve ACE gen polimorfizmleri çalışılmıştır. Apo E ve ACE genotipleri PCR (Polymerase Chain Reaction), RFLP (Restriction Fragment Length Polymorphism), ve agaroz jel elektroforez teknikleri kullanılarak tespit edilmiştir. Plazma malondialdehit (MDA) düzeyleri spektrofotometrik olarak saptanmıştır. Bulgular: Çalışmamızda Apo E e4 allelini taşıyan hastalarda (7.49±3.26 nmol/ml) malondialdehid seviyesi taşımayanlara göre (5.6±2.5 nmol/ml) istatistiki açıdan anlamlı olarak artmış bulunmuştur (p
Demansiyel Olgularda Apolipoprotein E ve Angiotensin Konverting Enzim Gen Polimorfizmlerinin Plazma Malondialdehid Düzeyleri ile İlişkisi